The Teaching Challenges: Novice Teachers of Literature's Experience - Daoudi ,Wahiba; Boumediene, Houda (University of Ammar Theledji -Laghouat, 2020)
Teaching English literature has lately proven to be a motivating and challenging experience for novice teachers who may face numerous problems at the beginning of their career. The core of our study was to investigate the problems encountered in the teaching/learning process by both novice teachers of literature and their students. The matter that called us to follow up on the topic, investigate it, discuss its problems and to answer this main question: What are the main difficulties that novice teachers of literature face at English classes? The research approach in this study was a mixture of quantitative and qualitative frameworks. Our study fell with the descriptive-analytical research and for that, we choose a sample randomly selected. We seek to know teacher-related problems and student-related problems through the analysis and interpretations of research tools in which an online questionnaire and semi structured interview were distributed to novice teachers and master students at the Department of English at Ammar Thelidji University. The findings of the research revealed that novice teachers face problems such as choosing the appropriate teaching method that better suits the learners' needs, the lack of library sources, and drawing students' attention, these all were due to the lack of experience and training in literature teaching. Moreover, this research found out that students have problems too, from teachers' perspectives, such as the low level of language proficiency and the lack of background knowledge in literature. Therefore, this study recommends further researches on the training and its importance for novice teachers of English Literature